PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERNAL, DAN KOMITMEN ORGANISASI. TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Pradnyandari Gusti Ayu Made Gangga Putri; Putra Cokorda Gde Bayu (UNHI Press, 2022)
Local Government Financial Reports (LKPD) are intended to fulfill the general purpose of financial report. LKPD’s quality each year will receive an assessment in the form of an opinion from the Supreme Audit Agency (BPK). The population used in the research were every employees that worked inside the OPD Tabanan Regency as many as 2700 people. To determine the samples, the researcher used purposive sampling method to obtain 128 people as the samples. After testing the instrument and classical assumption test, researcher are using multiple linear regression, , F also t test, and determination test to analyze the data. Analyzing results showed human resource competence positively influenced the OPD financial reports quality in Tabanan Regency, the system Internal control has an effect positively on the OPD financial reports quality in Tabanan Regency, organizational commitment has positive effects on OPD financial reports quality in Tabanan Regency.